CHANGE OF GENETIC CHARACTERS IN PLANTS, GENETIC ANALYSIS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article provides detailed information on the inheritance and variability of genes in plants, biochemical processes, molecular genetic methods, mutational and hybridological analysis, combination or recombination, mutagenesis, aneuploidy, genetic studies.